2021
DOI: 10.9734/ajbgmb/2021/v8i130185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Haematological Indices of Local and Exotic Turkeys Inoculated with Attenuated Salmonella typhimurium Vaccine

Abstract: Infection due to Salmonella spp is one of the threatening diseases to poultry industry because it can cause economic losses through mortality, morbidity and reduction in egg production. One hundred and sixty poults comprising 80 local and 80 exotic (Nicholas white) were used to examine the variations in haematological response to Salmonella spp in local and exotic turkeys inoculated with attenuated Salmonella spp. Both genotypes were reared separately on deep litter, under the same management practices and win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…On the other hand, the global human health impact of nontyphoidal Salmonella is high, with an estimated 93.8 million cases, of which an estimated 80.3 million are food-borne, and 155.000 deaths each year [ 4 ]. Salmonellosis is an important source of morbidity [ 5 ]. Their clinical picture varies from a common gastroenteric to enteric fevers, which are life-threatening, requiring prompt and correct antibiotherapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the global human health impact of nontyphoidal Salmonella is high, with an estimated 93.8 million cases, of which an estimated 80.3 million are food-borne, and 155.000 deaths each year [ 4 ]. Salmonellosis is an important source of morbidity [ 5 ]. Their clinical picture varies from a common gastroenteric to enteric fevers, which are life-threatening, requiring prompt and correct antibiotherapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hematological parameters have been observed as good indicators of the physiological status of the animal and their changes are important in assessing the response of such animals to various physiological situations 13 . In the current study, the results of haematological analysis showed that broilers used for the study were not affected by genotypes before inoculation with the Eimera tenella vaccine except in LYMP and MCV.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low production of turkey in Nigeria, its consumption is relatively increasing just like chicken and other animal products. However, unlike chicken, turkey production has not gained much popularity in Nigeria; its demand is majorly dependent upon its importation as frozen food [5]. The need for profound research in turkey production in Nigeria is necessitated by its valuable meat with its high rate of economic return.…”
Section: Introductionmentioning
confidence: 99%